Effect of Nebulized Lignocaine on Prevention of Postoperative Sore Throat following Laparoscopic Cholecystectomy - Bajracharya, Ashis Ratna; Bajracharya, Gautam Ratna; Thapa, Chitra; Bhandari, Sabin (Nepal Medical College Journal, 2024)
Post-operative sore throat (POST) is one of the common side effects of general anesthesia with endotracheal intubation. Several medications have been tried for the prevention of POST. Nebulized lignocaine is easily available, easily administered, cost-effective, and acts immediately with a short duration of action and minimal systemic effects with no long-term residual effects. We conducted this study to find the prevalence of POST when preoperative nebulization with 2% lignocaine is used in patients following laparoscopic cholecystectomy. We also studied the factors associated with POST. This study was done in 100 patients who underwent laparoscopic cholecystectomy and received preoperative lignocaine nebulization. The incidence of POST was measured at 0, 6, 12, and 24 hours postoperatively and various risk factors that might have predisposed for the development of POST were also studied. The mean age of the patients was 42.53±12.82 years. A total of 40 patients (40.0%) experienced POST at any time point during the study period. The majority of patients had mild i.e. Grade 1 POST (11-21%). Patients with a BMI > 30 kg/m2, CL grade 4, high cuff volume, airway trauma, higher duration of intubation, and higher pneumoperitoneum duration had a greater incidence of POST at all post-operative periods. We concluded that nebulization of 5 ml of 2.0% lignocaine decreases the intensity and treatment requirement for POST and has minimal side effects. A higher incidence of POST is seen in patients who had a higher CL grading, higher BMI, high cuff volume, airway trauma, higher duration of intubation, and longer pneumoperitoneum duration.